The learning of English language using online platforms among English as a second language learners in the Philippines: Stress and coping strategies - Judith, Vanessa Joy Z. (Edelweiss Applied Science and Technology, 2025)
Language learning among ESL students is a complex process that often leads to stress. Moreover, coping strategies are a person’s choices to respond to a stressor. This study examined English language learning via online platforms among ESL students in the Philippines, focusing on stress levels and coping strategies. Using a descriptive research method, 165 ESL students from a state university in Central Philippines were surveyed using validated instruments. Data analysis involved mean, standard deviation, t-test, ANOVA, and Pearson’s r, with sex and year level as variables. Findings showed that female ESL learners experienced higher stress. Coping strategies were moderate across all groups. Significant differences in stress and coping mechanisms were noted between the sexes. A relationship between stress levels and coping mechanisms was also evident. Practical implications include tailoring support for female ESL learners. Targeted support for them has to be implemented, such as stress management workshops integrated into online language learning. To address the variation in stress levels caused by differences in sex, there is a need to conduct gender-specific stress management sessions and identify coping mechanisms that are unique to each gender.